MEMAKNAI KERJA BERLANDASKAN ALKITAB DI INSTITUSI PENDIDIKAN KRISTEN - Feteriadi F (Jurnal Theologia Forum STFT Surya Nusantara, 2018)
The word “Work” in English is divided into three: job, career, and vocation. A job is a work that someone does to get something in return. On the other hand, career is the development and progress (position or rank) of a person in his/her work. Finally, someone who does a specific work according to their calling based on God’s will is called a vocation. The meaning of work on this paper is vocation. Working is a part of someone's life. A person can not have a meaningful life when they are not working, and it doesn’t mean that everyone who works has a meaningful life. The purpose of this paper is to discuss the meaning of work, what is the purpose of working, and is work done to fulfill the survival instinct?. How do we make work meaningful? What are the implications of work towards the enhancement of quality in an institution? How do you recruit employees who embody the definition of work? How do employees working in UPH can be guided well so that they could perceive meaningful work? The author conducted a survey of one hundred new employees who just recently joined UPH, on how far do they define a meaningful work. Most of them did not have the awareness of the importance of defining work. The author took this as an opportunity to develop employees who have yet understand the meaning of work. With this, it opens up opportunities for the institution of UPH to continuously improve the quality, for the meaning of work has a direct implication on the quality of education in UPH.